Field and laboratory methods in primatology a practical guide - Setchell, Joanna M. 1973-; Curtis, Deborah J. 1964- (Cambridge University Press, 2003)
Field and Laboratory Methods in Primatology is a manual for students and researchers studying wild primates. Technological advances allow fieldworkers to collect a wide range of data, store samples for later analysis, and collect information remotely. These methods open up opportunities to gain new insights on previously studied populations and are the means of collecting data on species that have, until now, been difficult to study. However, information on the practicalities of using such methodology in the field has largely been lacking. Here, in this indispensable reference, experienced fieldworkers provide the first comprehensive guide to the wide variety of techniques available for the study of wild primates. Covering everything from pre-trip planning to laboratory analysis of endocrine and genetic samples, packed full of tips and emphasising practicalities and ethics throughout, it is a must-have for all field primatologists and others studying free-ranging animals